Racing stripes [videorecording (DVD)] - Du Chau, Frederik; Muniz, Frankie, 1985-; Moore, Mandy, 1984-; Duncan, Michael Clarke (Warner Home Video, 2005)
A traveling circus accidentally leaves behind a baby zebra. The baby is then rescued by horse farmer Nolan Walsh, who takes him home to his young daughter Channing. "Stripes" is soon introduced to the farm's misfit troupe of barnyard residents. The Walsh farm borders the Turfway Racetrack, where highly skilled thoroughbreds compete for the ultra-prestigious Kentucky Crown. From the first moment Stripes lays eyes on the track, he's hooked. He knows that if he could just get a chance, he could leave all those other horses in the dust. What he doesn't know is - he's not exactly a horse. But with characteristic zeal, he devotes himself to training for the big time.